2011
DOI: 10.1111/j.1525-1446.2011.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Counseling for Parents During Child Hospitalization: A National Survey of Pediatric Nurses

Abstract: Future research should test the efficacy of developing comprehensive hospital-wide policies to deliver smoking cessation for parents during a child's hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
(25 reference statements)
4
22
1
Order By: Relevance
“…[19][20][21][22] Although national respiratory and nursing associations and others have long advocated for regular provision of tobacco cessation interventions by their members, [26][27][28][29][30][31][32][33] pediatric RTs and RNs still do not use their patients' visits to motivate parents to quit smoking. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Our study provides additional evidence to support this claim. It also showed that, before enrolling in WeBREATHe, participating RTs and RNs asked parents about their tobacco use only some of the time and almost never provided any type of assistance.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…[19][20][21][22] Although national respiratory and nursing associations and others have long advocated for regular provision of tobacco cessation interventions by their members, [26][27][28][29][30][31][32][33] pediatric RTs and RNs still do not use their patients' visits to motivate parents to quit smoking. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Our study provides additional evidence to support this claim. It also showed that, before enrolling in WeBREATHe, participating RTs and RNs asked parents about their tobacco use only some of the time and almost never provided any type of assistance.…”
Section: Discussionsupporting
confidence: 82%
“…[26][27][28][29][30][31][32] Although RTs, RNs, and NPs are interested in addressing tobacco use with patients, few incorporate cessation into routine care. 23,29,[33][34][35][36][37][38] Many lack confidence in providing cessation advice and fear that they may antagonize and alienate the smoker. 36,39 Provision of tobacco cessation intervention training and self-help materials can offset these concerns.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These barriers include lack of visit time and reimbursement for these services, lack of infrastructure for parental tobacco screening and counseling, and most notably, lack of practitioner comfort in counseling adult smokers. 16,17 …”
mentioning
confidence: 99%
“…7 Using nursing staff has been shown to be feasible and effective in both adult and pediatric inpatient settings. [7][8][9][10][11] Quitlines are a key component of tobacco control by providing telephone counseling, nicotine replacement therapy, and Webbased resources and support. Quitlines have been shown to be a highly costeffective intervention, delivering high value relative to cost when compared with other common disease prevention interventions and medical treatments.…”
mentioning
confidence: 99%